Natural attenuation model and biodegradation for 1,1,1-trichloroethane contaminant in shallow groundwater - Lu, Qiang; Zhu, Rui-Li; Yang, Jie; Li, Hui; Liu, Yong-Di; Lu, Shu-Guang; Luo, Qi-Shi; Lin, Kuang-Fei (Frontiers in Microbiology, 2015)
Natural attenuation is an effective and feasible technology for controlling groundwater contamination. This study investigated the potential effectiveness and mechanisms of natural attenuation of 1,1,1-trichloroethane (TCA) contaminants in in Shallow Groundwater in Shanghai by using a column simulation experiment, reactive transport model, and 16S rRNA gene clone library. The results indicated that the majority of the contaminant mass was present at 2-6 m in depth, the contaminated area was approximately 1000 m2, and natural attenuation processes were occurring at the site. The effluent breakthrough curves from the column experiments demonstrated that the effectiveness of TCA natural attenuation in the groundwater accorded with the advection-dispersion-reaction equation. The kinetic parameter of adsorption and biotic dehydrochlorination of TCA was 0.068 m3/kg and 0.0045 d-1. The contamination plume was predicted to diminish and the maximum concentration of TCA decreased to 280 μg/L. The bacterial community in situ groundwater belonged to Trichococcus, Geobacteraceae, Geobacter, Mucilaginibacter and Arthrobacter.